Efficient power generating devices utilizing low intensity indoor lights via non-radiative energy transfer mechanism from organic ionic redox couples. (June 2019) - Vaghasiya, Jayraj V.; Sonigara, Keval K.; Suresh, Lakshmi; Panahandeh-Fard, Majid; Soni, Saurabh S.; Tan, Swee Ching
Abstract: Low intensity indoor lightings are often wasted and unutilized, when they could be harvested to produce electrical energy. Unfortunately there is currently no solar cells which could harvest low light intensity efficiently. Therefore, this work reports the synthesis of energy transfer redox couples (ETRCs) that aid in the harvesting of low light intensity for photoelectrochemical cells. Such ETRCs are excellent choices as electrolytes in solid-state photoelectrochemical cells owing to their multifunctional attributes like faster dye regeneration, more efficient light absorption and faster energy transfer kinetics. Electrochemical characterizations reveal that Forster Resonance Energy Transfer (FRET) is occurring between ERTC electrolyte (donor) and the N719 dye (acceptor). Photovoltaic efficiency of the reported device is 28% higher than the conventional silicon solar cells, tested under low light intensity. Additionally, the idiosyncratic design of this device makes it versatile to be used in indoor conditions or can be mounted at a wide range of incidence angle with an ability to retain a high efficiency of 21.08%. Superior ionic-conductivity imparted by the single-component electrolyte provides a platform for future directions in energy harvesting and storage. Graphical abstract: Image 1 Highlights: New organic-ionic redox couple based DSSCs with a unique property to harness low intensity indoor lights. Single component organic ionic conductor owns dual nature; one as a redox mediator and other as a light harvester. ETRC-1 based DSSC exhibited highest efficiency of 21.0% under low-light intensity owing to FRET mechanism. FRET mechanism reported for the first time between electrolyte/photosensitizer without any secondary additive.